This really depends on the fraction; if there are variables in the equation, if they are full numbers,etc. I'd really recommend looking up khan academy on YouTube and that will really help you out!
<span>3(x+4)^2-24=0
</span>
<span>3(x+4)^2 = 24
</span>
<span>(x+4)^2 = 24/3
</span>
<span>(x+4)^2 = 8
</span><span>
</span><span>(x+4)² = (2√2)² ⇒ x+4 = 2√2 ⇒ x = 2√2 - 4
</span>
Answer:
The real solutions are
![x=\sqrt[6]{6}\approx 1.35\\\\\:x=-\sqrt[6]{6}\approx -1.35](https://tex.z-dn.net/?f=x%3D%5Csqrt%5B6%5D%7B6%7D%5Capprox%201.35%5C%5C%5C%5C%5C%3Ax%3D-%5Csqrt%5B6%5D%7B6%7D%5Capprox%20-1.35)
Step-by-step explanation:
The solution, or root, of an equation is any value or set of values that can be substituted into the equation to make it a true statement.
To find the real solutions of the equation
:
![\mathrm{Divide\:both\:sides\:by\:}5\\\\\frac{5x^6}{5}=\frac{30}{5}\\\\\mathrm{Simplify}\\\\x^6=6\\\\\mathrm{For\:}x^n=f\left(a\right)\mathrm{,\:n\:is\:even,\:the\:solutions\:are\:}x=\sqrt[n]{f\left(a\right)},\:-\sqrt[n]{f\left(a\right)}\\\\x=\sqrt[6]{6}\approx 1.35\\\\\:x=-\sqrt[6]{6}\approx -1.35](https://tex.z-dn.net/?f=%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D5%5C%5C%5C%5C%5Cfrac%7B5x%5E6%7D%7B5%7D%3D%5Cfrac%7B30%7D%7B5%7D%5C%5C%5C%5C%5Cmathrm%7BSimplify%7D%5C%5C%5C%5Cx%5E6%3D6%5C%5C%5C%5C%5Cmathrm%7BFor%5C%3A%7Dx%5En%3Df%5Cleft%28a%5Cright%29%5Cmathrm%7B%2C%5C%3An%5C%3Ais%5C%3Aeven%2C%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Dx%3D%5Csqrt%5Bn%5D%7Bf%5Cleft%28a%5Cright%29%7D%2C%5C%3A-%5Csqrt%5Bn%5D%7Bf%5Cleft%28a%5Cright%29%7D%5C%5C%5C%5Cx%3D%5Csqrt%5B6%5D%7B6%7D%5Capprox%201.35%5C%5C%5C%5C%5C%3Ax%3D-%5Csqrt%5B6%5D%7B6%7D%5Capprox%20-1.35)
Answer:
2s/n-a=L
Step-by-step explanation:
So first we divide (n÷2) so it will be s/(n÷2) =a+L. Next we subtract L and get s/(n÷2)-a. That's not it yet, since 2 is being divided in the denominator, we have to reciprocal it meaning multiply, it to the top value. So it would 2s/n-a=L. But you can just leave it like that if you desire and your teacher doesn't mind.
Answer:
$3
Step-by-step explanation:
Let chocolate pie be x and apple pie be y
Darryl made $38 from 2 chocolate pies and 4 apple pies
That’s
2x + 4y = $38
Kayla made $138 from 14 chocolate pies and 12 apple pies
That’s
14x + 12y = $138
We now have two equations
Equation 1 : 2x + 4y = 38
Equation 2: 14x + 12y = 138
Multiply equation one by 12 and equation 2 by 4 to eliminate apple pie y
We have
12 x 2x + 12 x 4y = 12 x 38
4 x 14x + 4 x 12y = 4 x 138
24x + 48y = 456
56x + 48y = 552
Subtract equation equation two from one
-32x = -96
Divide both sides by -32
x = -96/-32
x = 3
A chocolate pie cost $3